Isto é um negro?: uma tentativa de articular educação somática e criação artística - Castro, Tarina Quelho de (2021)
This dissertation is an attempt to articulate a path, crossed by somatic education, in which the artistic and pedagogical dimensions are mixed and complexified, insofar as learning is always a movement of creation (I need to invent what I learn), just as any process of creation implies a change of perspective, a transition from one point of understanding to another, which we could use as a possible definition of learning. My object of study is the work Is this a Negro? (IEUN) , which I directed and created in collaboration with Mirella Façanha, Palomaris Mathias, Gian Melone, Lucas Wickhaus, Lucas Brandão, José Fernando Peixoto de Azevedo and Francisco Lauridsen Ribeiro